Determinação analítica, estudo cinético e produtos de degradação do antibiótico doripenem - Barbosa, Fábio de Souza (2015)
Doripenem is a β-lactam antibiotic with a broad spectrum of antimicrobial activity, including gram-negative strains, and producers of extended spectrum β-lactamases (ESBL) and ampC β-lactamases ampC. Despite its great clinical importance, carbapenems do not show good stability when incorporated as solution, as reported in several studies. In reference to doripenem, several works have describing its clinical use, efficacy data and cases of resistance. However, few works mention the drug stability, in terms of degradation products and routes of decomposition. The present work aimed to develop and validate a stability-indicating method by ultra-fast liquid chomatograph (UFLC) for doripenem in powder for injection, purposing an evaluation of stability of reconstituted solution using stress conditions of heat, oxidation, acid hydrolysis, alkaline hydrolysis and photolysis. The chemical kinetic of decomposition was also assayed for thermal and oxidative degradation. For identification of degradation products, the degraded samples where submitted to analysis by LC-MS. The chromatographic method described here proved to be stability-indicating and suitable for the determination of doripenem in drug formulation. The method linearity was performed in the range of 5 to 40 g mL-1, whose correlation coefficient (r) was 0.9999. The robustness testing, assayed against a variety of factors, allowed verifying that the method accept small variations in routine analysis. The forced degradation demonstrated the susceptibility of doripenem to several decomposition factors, being intense the instability to acidic and alkaline hydrolysis. In basic media, the drug residual content was approximately 40% in 2 minutes. At oxidative decomposition, the drug follows second-order kinetics, with a rate reaction of 0.000086 and 0.00010 %-1 min-1, respectively for H2O2 at 3.0 and 10.0 %. The thermal decomposition showed an activation energy of 15 kcal mol-1, a characteristic value for hydrolysis reactions. The analysis by LC-MS revealed that the major degradation products formed under oxidizing conditions and thermolysis present molecular weight (411, 427, 437, 634, 650 and 664). The stability of doripenem must be carefully observed, mainly after reconstitution and storage in adverse conditions of temperature.